Case Report: Countermeasures Against Heat and Coronavirus for Japanese Athletes at the Tokyo 2020 Olympics and Paralympic Games - Nakamura, Mariko; Naito, Takashi; Saito, Tatsuya; Takahashi, Akari; Muraishi, Koji; Hakamada, Noriko; Otomo, Mana; Iizuka, Satoshi; Nakamura, Daisuke; Takahashi, Hideyuki (Frontiers in Sports and Active Living, 2022)
The Tokyo 2020 Olympics and Paralympic Games were held in the hottest environment in the history of the games. Additionally, the worldwide coronavirus disease 2019 (COVID-19) pandemic necessitated daily polymerase chain reaction (PCR) testing during the games, wearing a mask became mandatory publicly, and it was an unheard and unique Olympic with no spectators. Heat acclimation, hydration, and body cooling are essential for safe and high-performance activities in hot environments. In 2015, the Japan Institute of Sports Sciences launched the “Heat Countermeasure Project” to conduct experiments and practical research on heat countermeasures and investigate issues related to heat countermeasures in each athletic event. The results obtained were proposed to various Japan national sports teams, and support for heat countermeasures for the Tokyo 2020 games was promoted in consultation with national federations. Furthermore, due to the COVID-19 pandemic, infectious disease countermeasures for the Tokyo 2020 Games during support were a must. Moreover, athletes, coaches, and team staff could not avoid implementing heat countermeasures while adopting measures against infectious diseases. This study aimed to clarify the issues faced with heat countermeasures and report on heat acclimation training and cooling support efforts, considering measures against infectious diseases.